Systematic anthropological approach in the treatment of acute and recurrent stages in patients with psoriasis - Terekhov, G. V.; Chukhraev, V. N.; Zukow, W. (Journal of Education, Health and Sport, 2018)
The article describes a new technology is the treatment of acute and relapsing phases in patients with psoriasis based on the use of multilevel system antropological approach consisting of psychosomatic correction of the patient by methods magnetolaser and neuroacustic stimulation of the central nervous system on the basis of personalized program in combination with compensation aerobic starvation by applying endonasal respiration singlet-oxygen mixture in a magnetic field and a decrease in cutaneous manifestations of pathological changed d on the basis of no injection transdermal administration autoplasma blood by pulsed electrophoresis in a magnetic field.